2021
DOI: 10.1039/d1cp00409c
|View full text |Cite
|
Sign up to set email alerts
|

The many-body expansion for aqueous systems revisited: III. Hofmeister ion–water interactions

Abstract: We report a Many Body Energy (MBE) analysis of aqueous ionic clusters containing anions and cations at the two opposite ends of the Hofmeister series, viz. the kosmotropes Ca2+, SO42-...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 87 publications
1
19
0
Order By: Relevance
“…Hence, the occurrence of a higher energy configuration of the water molecules may have been responsible for accelerating the evaporation process for chaotropes. The present argument of lower/higher energy configuration of water molecules in the presence of Hofmeister ions is further supported by the computational studies by Herman et al and Heindel et al, where the kosmotropic and chaotropic anions are involved in enhancing and reducing the binding energies of the aqueous clusters (Table S5).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Hence, the occurrence of a higher energy configuration of the water molecules may have been responsible for accelerating the evaporation process for chaotropes. The present argument of lower/higher energy configuration of water molecules in the presence of Hofmeister ions is further supported by the computational studies by Herman et al and Heindel et al, where the kosmotropic and chaotropic anions are involved in enhancing and reducing the binding energies of the aqueous clusters (Table S5).…”
Section: Resultssupporting
confidence: 79%
“…The ability of kosmotropes and chaotropes to make strong/weak H-bonded water structure can be understood as follows: It is known that due to the small size and low polarizability, the kosmotrope anions are repelled from the interface and are strongly hydrolyzed . Because of the high charge density of kosmotropes, the water molecules in their surroundings are closely packed and thus use the configuration to make a strongly H-bonded network. , However, with the large size and high polarizability, the chaotropes are known to get adsorbed at the interface where the ions lose part of their hydration sheath, resulting in weakly H-bonded water molecules. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the latter is understood as a many-body contribution consisting of the sum of all contributions from three-body to n-body, depending on the number of bodies (molecules), n , in the molecular chain. For more about the many-body approach, see a collection of papers and references therein [ 77 , 78 , 79 , 80 , 81 ]. There are a few extensions of BSSE correction (basis set superposition error) to the many-body approach, but in general they give several numerical problems, including negative values of some n-body BSSE corrections.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments and computations of NaCl ion-pairs in clusters have been mainly performed in systems composed of up to a few tens of H 2 O molecules. Fourier transform microwave spectroscopy has shown that the distance between the ions in a NaCl pair increases by gradually adding up to 3 H 2 O molecules and reaches the value of 2.9 Å, which is the contact-ion pair (CIP) distance found in the bulk solution. Anion photoelectron spectroscopy of clusters comprising NaCl and up to 12 H 2 O molecules found that at 9–12 H 2 O molecules, the CIP and SSIP (solvent-separated ion pair) formations are almost degenerate in energy.…”
Section: Introductionmentioning
confidence: 99%